A method for inverting the touchdown shock of the Philae lander on comet 67P/Churyumov-Gerasimenko. (February 2015) - Faber, Claudia; Knapmeyer, Martin; Roll, Reinhard; Chares, Bernd; Schröder, Silvio; Witte, Lars; Seidensticker, Klaus J.; Fischer, Hans-Herbert; Möhlmann, Diedrich; Arnold, Walter
Abstract: The landing of Philae on comet 67P/Churyumov-Gerasimenko is scheduled for November 12th, 2014. Each of the three landing feet houses in one sole a tri-axial acceleration sensor of the Comet Acoustic Surface Sounding Experiment (CASSE). They will thus be the first sensors to be in mechanical contact with the comet surface. CASSE will be in listening mode to record the deceleration of the lander when it impacts with the comet at a velocity of approx. 1 m/s. The signals are used to discern from these data whether the selected landing place is of icy or sandy nature. Here, a deeper analysis of this data yields information on the reduced elastic-plastic modulus of the comet׳s surface material. Highlights: Inverting Philae's deceleration signals to measure surface elastic/plastic properties of 67P. Exploitation of the foot-sole's contact-resonances to obtain elastic/plastic surface data of 67P. Calibration of the deceleration signals on stiff and soft materials.